Impact of coarse aggregate on compressive strength of concrete / Jeriscot H. Quayson and Zakari Mustapha. - Quayson, Jeriscot H.; Mustapha, Zakari (Faculty of Architecture, Planning and Surveying (FSPU) and UiTM Press Universiti Teknologi MARA (UiTM), Selangor, Malaysia., 2019)
Over one-third of the volume of concrete is occupied by coarse aggregate and any changes in coarse aggregate type can affect its strength and fracture properties. The paper examined the impact of coarse aggregates on compressive strength of concrete. Slump and compaction factor tests were conducted on the mixture of quartzite and crushed granite course aggregates, and quarry dust (fine aggregate). Nominal mix (1:2:3) was adopted and mix compositions were calculated by absolute weight method. Twelve (12) cubes (150x150mm) of each type of coarse aggregate were cast for 7, 14, 21, and 28 days to determine their compressive strengths. Quartzite was found to have the highest average compressive strength of 24.48N/mm2 with an average density of 2160kg/m3 , while compressive strength of crushed granite was 22.01N/mm2 with an average density of 2300kg/m3 on the 28 day of testing. Concrete made from granite had the highest workability, while concrete made from quartzite aggregate had the highest compressive strength. Densities and compressive strengths of the individual aggregates accounted for the variation in strengths of the concrete, due to differences in properties and strengths. In conclusion, the effect of any type of coarse aggregate on the compressive strength of concrete will be known and also enable contractors to determine the type of aggregate to be selected for a particular work.